A Semantic Analysis of Selected Nigerian Newspaper Reports on the Effect of the 2023 Naira Redesign - Obasi, Jane Chinelo; Obielo, Sandra Chinenyenwa (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This study is a semantic analysis of news reports on the effect of the 2023 Nigerian Naira redesign from selected Nigerian newspapers. A total of 40 news reports were purposively sampled from four Nigerian newspapers (The Sun, Vanguard, The Guardian and Premium Times). Fillmore’s (1982) Frame Semantic Theory, which proposed that language is composed of semantic frames, which are mental representations of situations or scenarios, was adopted for this study. A qualitative research design was employed in the data analysis to examine the elements of Frame Semantic Theory evident in the extracted data. The findings revealed that all the four newspapers consistently framed the effects of the Naira redesign within the context of economic hardship. It also revealed that the newspapers predominantly conveyed negative perspectives regarding the Naira redesign. The cross-newspaper comparative analysis also highlighted the widespread and varied effects of the Naira redesign.